The Character Education through Moral-Philosophical Approach of The Wonderful Wizard of Oz Novel for Indonesian Student - Ni Ketut Ayu Wiranti; Dewa Ayu Eka Agustini; Putu Adi Krisna Juniarta (ID Solutions, 2021)
The conditions that occur in Indonesia, such as environmental damage, promiscuity, etc., it is one of the important factors in the formation of moral values today starting from school. The character building become the important part in the term of learning process in Indonesia. Indonesian government made Peraturan Menteri Pendidikan Dan Kebudayaan Republik Indonesia Nomor 20 Tahun 2018 Tentang Penguatan Pendidikan Karakter Pada Satuan Pendidikan Formal or Permendikbud No. 20 of 2018 about Strengthening Character Education in Formal Education Units to make the character education is very important. The aims of this research is to describe and analyse the character education values contained in The Wonderful Wizard of Oz novel by L. Frank Baum. Descriptive qualitative research used to uses. The technique of data collection uses the document data. Data analysis techniques used in qualitative research include data reduction, analysis, data interpretation and triangulation. The result conveys about there are ten character education value contained in The Wonderful Wizard of Oz novel such as: honesty, tolerance, work hard, creative, love the motherland, communicative, love for peace, care for environment, social care, and be responsible.